Addressing health inequalities in diabetes through research: Recommendations from Diabetes UK's 2022 health inequalities in diabetes workshop. Issue 4 (19th December 2022) - Chan, Jodie; Blane, David; Choudhary, Pratik; Chowdhury, Tahseen A.; Goyal, Aaliya; Hanif, Wasim; Jacca, Joyce; Mathur, Rohini; Misra, Shivani; Ocran, Nana; Rutter, Martin K.; Studley, Ruth; et al.
Abstract: Aims: To develop a position statement which identifies research priorities to address health inequalities in diabetes and provides recommendations to researchers and research funders on how best to conduct research in these areas. Methods: A two‐day research workshop was conducted bringing together research experts in diabetes, research experts in health inequalities, healthcare professionals and people living with diabetes. Results: The following key areas were identified as needing increased focus: How can we improve patient and public involvement and engagement to make diabetes research more inclusive of and relevant to diverse communities? How can we improve research design so that the people who could benefit most are represented? How can we use theories from implementation science to facilitate the uptake of research findings into routine practice to reach the populations with highest need? How can we collate and evaluate local innovation projects and disseminate best practice around tackling health inequalities in diabetes? How can we best collect and use data to address health inequalities in diabetes, including the harnessing of real‐world and routinely collected data? How could research funders allocate funds to best address health inequalities in diabetes? How do we ensure the research community is representative of the general population? Conclusions: This position statement outlines recommendations to address the urgent need to tackle health inequalities in diabetes through research and calls on the diabetes research community to act upon these recommendations to ensure future research works to eliminate unfair and avoidable disparities in health.